PERANCANGAN STANDART OPERATIONAL PROCEDURE PRODUKSI PADA PERUSAHAAN COFFEEIN - Tanujaya, Chesley (PERFORMA, 2017)
Recently, the industry of coffee beverage is developing in Surabaya. Coffeein is one of the companies that is developing, therefore there is a design of SOP to make the company have working instruction policy. The purpose of this research is to design the SOP of Coffeein production to be the company production guidance. This research type is qualitative research. The sample and population that are used in this research is the similar entrepreneur, the leader of Coffeein company, and the expert of SOP. The validity test data in this research yet triangulation source. Data analysis technique user template that filled with flowchart and be a draft. This research result shows that SOP can be the basic working instructionof the employees even the owner of the company and help the evaluation of employees performance.